Selective Attention and Fear of Cancer Recurrence in Breast Cancer Survivors. Issue 1 (17th May 2014) - Custers, J. A. E.; Becker, E. S.; Gielissen, M. F. M.; Van Laarhoven, H. W. M.; Rinck, M.; Prins, J. B.
Abstract: Background: Anxious people show an attentional bias towards threatening information. Purpose: It was investigated whether an attentional bias exists for cancer-related stimuli in breast cancer survivors and if different levels of fear of cancer recurrence would lead to different patterns of selective attention. Methods: Breast cancer survivors with high ( n = 35) and low ( n = 32) fear of cancer recurrence were compared to 40 healthy female hospital employees. Specificity of attentional biases was investigated using a modified Emotional Stroop Task. Self-report measures were used to assess depression and anxiety, feelings of fatigue, and experienced traumas. Results: Compared to control participants, breast cancer survivors with both high and low levels of fear of cancer recurrence showed increased interference for cancer-related words, but not for other word types. Conclusions: The findings suggest a specific attentional bias for cancer-related words in breast cancer survivors that is independent of level of fear of cancer recurrence.